“Students are Once Again ‘Numbers’ Instead of Actual Human Beings”: Teacher Performance Assessment and The Governing of Curriculum and Teacher Education. - Coloma, Roland Sintos (Journal of the Canadian Association for Curriculum Studies, 2015)
This paper will examine the educational experiences of teacher candidates and the use of teacher performance assessment (edTPA) to measure their quality, competence, and impact. It will situate edTPA within the national, politically-charged debate between the defenders and reformers of teacher education who advocate for the professionalization versus deregulation of the field, respectively. Their positions converge, however, in the collective belief and reliance on testing to measure educational inputs and outputs. Even the defenders are caught in a reactive stance to show through testing data the value and relevance of teacher preparation. The paper will also investigate the perspectives on edTPA of teacher candidates at a medium-sized, public university in the US Midwest. Using a survey of candidates who completed edTPA during the 2014-15 academic year, it will highlight candidate resistance to edTPA, even though they have been disciplined and immersed in a culture of testing throughout their K-12 and university education. Their resistance foregrounds three themes: (a) time and stress; (b) outsourcing of teacher evaluation; and (c) contradictions between curriculum and assessment in teacher education. Moreover, it will mobilize Michel Foucault’s concepts of governmentality and critique to analyze the ruling logic and practices in education and the candidates’ resistance under difficult conditions.